Administrative and legal aspects of the activity of the High anti-corruption court and other anti-corruption bodies of Ukraine in the context of europeanization - Kosiuta, Mykhailo; Sopilnyk, Lyubomyr; Denys, Solomiya; Sopilnyk, Rostyslav; Zayats, Roman (Global Prosperity, 2021)
The establishment of the High Anti-Corruption Court in Ukraine was a radical step for Ukraine in the fight against corruption. This fact has led to many discussions and debates in scientific circles. The purpose of the article is to administrative and legal characteristics of the legal status of the High Anti-Corruption Court and other Anti-Corruption Bodies of Ukraine and prospects it’s activity in the context of Europeanization. The chosen methodology helped to identify the historical origins of corruption; to outline the main features and establish the concept of “corruption”; to analyze the experience of European countries in establishing a system of anti-corruption bodies; to make proposals for reforming the current system of anti-corruption bodies of Ukraine in the context of Europeanization of administrative law. We believe that a key point in the process of improving the effectiveness of the fight against corruption in Ukraine is the need to implement the experience of European countries also in terms of informing and training civil servants professional ethics, awareness and legal culture. The high authority of anti-corruption bodies, as evidenced by the analyzed practice of EU countries (including Denmark), determines the effectiveness of the fight against corruption. Such a system of anti-corruption institutions will help to clearly establish powers, avoid conflicts of interest and bureaucratic schemes, increase the targeted use of budget funds, facilitate citizens’ access to relevant bodies with complaints about corruption offenses, and eliminate the privileged status of corrupt officials in the administration of justice.